Working Capital Management and Firms’ Performance: An Analysis of Sri Lanka Manufacturing Companies . - Koperunthevy, K. (Wayamba University of Sri Lanka., 2010)
A managerial accountings strategy focuses on maintaining efficient levels of both components of working capital, current assets and current labilities. Implementing and affective working capital management system is an excellent way to improve earnings. Prier evidence has determined relation between working capital and performance. This study extends the literature. The working capital is determined by the cash conversion Cycle and position of working capital, indicated by the current Ratio, quick ratio, stock to current assets and debtors to current assets. The performance is measured by return on total assets, and relation between working capital management and profitability is investigated by using panel data analysis for a sample of 50 investment in inventories and receivables lead to lower profitability and current assets to total assets lead to higher profitability. The results conclude that a strong relationship between working capital management and performance.
Keywords: Working capital management; Performance; Current assets; Current liabilities